PENGARUH MODEL PEMBELAJARAN NUMBER HEAD TOGETHER (NHT) BERBANTUAN MEDIA WORDWALL TERHADAP HASIL BELAJAR SISWA PADA MATERI “INDONESIAKU KAYA BUDAYA” - Pasaribu, Elisa Febriani; Angin, Laurensia Masri Perangin; Tamba, Robenhart; Manurung, Imelda Free Unita; Siregar, Fajar Sidik (Universitas Negeri Medan, 2025)
This study aims to determine the effect of the Numbered Heads Together (NHT) learning model assisted by Wordwall media on students' learning outcomes in the topic